Bremsstrahlung emission from high power laser interactions with constrained targets for industrial radiography. (25th April 2019) - Armstrong, C. D.; Brenner, C. M.; Jones, C.; Rusby, D. R.; Davidson, Z. E.; Zhang, Y.; Wragg, J.; Richards, S.; Spindloe, C.; Oliveira, P.; Notley, M.; Clarke, R.; et al.
Abstract : Laser–solid interactions are highly suited as a potential source of high energy X-rays for nondestructive imaging. A bright, energetic X-ray pulse can be driven from a small source, making it ideal for high resolution X-ray radiography. By limiting the lateral dimensions of the target we are able to confine the region over which X-rays are produced, enabling imaging with enhanced resolution and contrast. Using constrained targets we demonstrate experimentally a $(20± 3)~\unicode[STIX]{x03BC}\text{m}$ X-ray source, improving the image quality compared to unconstrained foil targets. Modelling demonstrates that a larger sheath field envelope around the perimeter of the constrained targets increases the proportion of electron current that recirculates through the target, driving a brighter source of X-rays.